Islamizing Stem: A Curriculum Analysis of Integrating Tawhidic Values into Science Education in Malaysian Secondary Schools - Chak Sothy; Teboho Maseko; Ethan Tan (Islamic Studies in the World, 2026)
Background. The global discourse on STEM education frequently centers on secular, utilitarian objectives. However, in Muslim-majority nations like Malaysia, there is a significant movement towards the “Islamization of Knowledge,” which seeks to integrate theological principles with modern science. This initiative stems from a perceived disconnect between secular scientific pedagogy and the foundational Islamic worldview (Tawhid). This study addresses the gap in understanding how these Tawhidic values are practically embedded within the official Malaysian secondary school science curriculum.. Purpose. This study aims to critically analyze the Malaysian secondary science curriculum (KSSM) to identify, map, and evaluate the extent and method of Tawhidic value integration in STEM subjects. The objective is to determine how the philosophical goal of “Islamizing STEM” is translated into pedagogical content and instructional guides for educators. Method. A qualitative content analysis design was employed. The primary data consisted of official curriculum documents, including syllabi and textbooks for Form 1-5 Physics, Chemistry, and Biology. The analysis utilized a researcher-developed coding framework based on established models of Tawhidic integration in science. This framework was applied to identify explicit, implicit, and omitted instances of value integration. Results. The analysis reveals that Tawhidic integration is present but predominantly implicit and superficial. Integration is largely confined to introductory chapters or “enrichment” sidebars, often as simple Qur’anic verses related to natural phenomena. The core scientific content (e.g., mechanics, evolution, chemical processes) largely remains a discrete, secular domain. A significant gap exists between the curriculum’s stated philosophical aims and its practical, assessable content. Conclusion. While the Malaysian curriculum aspires to Islamize STEM, its current iteration achieves only a marginal integration of Tawhidic values. This creates a “dual-narrative” curriculum, failing to achieve a genuine epistemic synthesis. To be effective, integration must move from peripheral references to a structural embedding within core scientific concepts and pedagogical practices.